Sistem Penunjang Keputusan Penentuan Supplier Toko Sembako Aishar dengan Metode MABAC - Fuad Azril Syamil Bayasef; I Made Sugi Ardana (Faktor Exacta, 2025)
Objectively selecting the right supplier is a challenge for Aishar grocery store. When faced with several alternative suppliers, it takes considerable time to determine which one to choose. Four criteria are used for selection: quality, delivery time, price, and service, with the highest weighting in descending order. Quality is given the highest weighting because it directly impacts customer loyalty, while service is given the lowest score because it is only related to the store. The MABAC method can be used to objectively and quickly select alternatives. To facilitate implementation, a website-based application was created following the SDLC stages. Application testing was conducted using the blackbox testing method, comparing manual calculations with the application's output. The application is designed to be flexible and setup-based so that changes in criteria or weighting can still be applied. The example used in this study involved selecting five suppliers using four criteria. After assessing each supplier's criteria, alternative supplier A3, Ibu Ayin, was selected with a score of 40.0782.